Electron beam welding complex diagnostics automated system - Нікітенко, Є. В. (Proceedings of National Aviation University, 2013)
The structure of the system of technical diagnostics is investigated. The algorithm of technical diagnostic of electron beam welding complex, which serves as the basis for creation of automated system for technical diagnostics, is proposed